SYNCHRONIZATION MECHANISM IN SIMULTANEOUS INTERPRETING - Olimova, Dilfuza Zokirovna (Innovative Development in Educational Activities, 2023)
This article discusses the factors which make the synchronization mechanism in simultaneous interpreting work, highlighting the cognitive aspects of it. It describes simultaneous translation as a classic case of distribution of attention because it combines several cognitive tasks, the execution of which occurs more or less simultaneously.